Estetika Bunyi Sound Logo Netflix dalam Pembentukan Identitas Merek - Denny Alpan; Rafiloza Rafiloza (Musica: Journal of Music, 2026)
This study analyzes the contribution of sound aesthetics to brand identity formation through an auditory examination of the Netflix sound logo. The objective is to explain how structural and formal sonic qualities construct aesthetic perception and brand recognition. The research employs a descriptive qualitative method using repeated critical listening and analysis of musical elements, including timbre, rhythm, dynamics, intensity, and sonic atmosphere. The findings reveal that the sound logo consists of a brief percussive strike followed by harmonic resonance, forming a unified composition with strong unity, complexity, and intensity. Its compact and contrasting structure generates instant recognition while eliciting emotional responses that reinforce the audiovisual experience. These results demonstrate that sound aesthetics functions strategically as both an aesthetic medium and a corporate symbol, strengthening brand differentiation in the digital environment.